ECDIS: A European Perspective - Bessero, G.; Hecht, H. (The International Hydrographic Review, 2015)
This article reviews the European requirements connected with the implementation of ECDIS. It is a slightly modified version of a report prepared for an action on ECDIS and maritime transport launched in February 1994 within the framework of the European cooperation in the field of Scientific and Technical research (COST 326), under the aegis of the Directorate General for Transport of the European Commission.